ANALISIS PENINGKATAN STANDAR PELAYANAN MINIMAL PADA USIA PENDIDIKAN DASAR SELAMA PANDEMI COVID-19 DI PUSKESMAS ANDALAS KOTA PADANG - Yuni Afrianis; Chriswardani Suryawati; Wulan Kusumastuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
During the Covid-19 pandemic, the implementation of the MSS (Minimum Service Standards) program age of basic education was hampered. Andalas public health center is health center with the lowest achievement of basic education age MSS in Padang City in 2020 with an achievement of 0%. This study aims to analyze the anticipation of the Andalas public health center in Padang City in increasing the coverage of MSS for basic education age in 2021. This study uses a qualitative method through in-depth interviews with selected informants based on purposive sampling criteria. The aspects studied consist of input, process, and output variables. The results showed a lack of knowledge of officers related to Minister of Health regulations RI No. 4 of 2019, facilities and infrastructure are adequate, data collection in 2021 through nutritional status data sent by the school, July data collection was carried out via google form, services followed standard operating procedures, recording by schools, reporting sent to the Padang City Health Office, monev by the City Health Office and the Head of the Puskesmas. Andalas Health Center's efforts to pursue the 2021 target, if the pandemic ends, the puskesmas maximizes direct health checks, if the pandemic is not over, the puskesmas will conduct a health check through the google form. continue to run the program by complying with health protocols.The City Health Office is expected to conduct regular monitoring, build communication, cooperate with puskesmas, and strengthen sanctions if the MSS does not reach the target.